Supporting Scholarly Thinking in a Nordic Teacher Education Webinar Practice - Reneland-Forsman, Linda; Magnusson, Maria (Journal of University Teaching and Learning Practice, 2019)
With this study we have a twofold aim. Firstly, to develop a model for identifying and analyzing the status of students' scholarly thinking, and secondly to design and evaluate an educational practice with the aim of supporting these skills. A series of webinars connected researchers and students from Finland, Norway and Sweden and gave the students access to an authentic Network of researchers, otherwise not accessible to them. The webinars were recorded and an analysis, inspired by variation theory, were conducted in order to identify signs of scholarly thinking in student reasoning when discussing students' final thesis. Findings were then used to construct a model for identifying variations of scholarly thinking as qualities of scholarly discernment, identified in students’ communicative actions. Two critical aspects for stimulating scholarly thinking during webinars emerged from data. First the diversity of language and knowledge and secondly, a more informal framing. A carefully staged webinar using these two critical aspects, offers a socialization of students in professional training, to an academic discourse where the production and evaluation of knowledge is part of students’ identity and constantly debated.